Spectral changes in electrical activity of pylorus due to L-NAME induced hypertrophic pyloric stenosis - Aslan, M.; Celik, O.; Dogan, D. G.; Tagluk, M. E.; Ulas, M.; Aydin, E. (Comenius Univ, 2011)
Objectives: To investigate the relation between hypertrophic pyloric stenosis (HPS) and the changes in the myoelectrical activity of the pyloric and gastric areas. Methods: Three pregnant females, at 14 days of gestation two of which were named as D14n (NOS inhibitor group) and one was named as D14c (control). From the beginning of the study until the end of gestation, rats in D14n group received nitric oxide synthase inhibitor L-NAME for administrating their pups, and the rat in D14c group was drinking water for 21 days. The pups of each group underwent laparotomy at 42 days of their life and myoelectrical signals of their pyloric and gastric regions were recorded via bipolar electrodes and then evaluated through signal processing. Results: Signal analysis showed that HPS induced pyloric segment reveals a suppressed spectral component that was detected in normal pyloric segment. The HPS induced pyloric segment also revealed higher power/min and +/- SD compared to that of normal and gastric areas. In the pyloric segment, while the number of interstitial cells of Cajal (ICC) was lesser, the number of smooth muscle cells was higher than in the pyloric segment of controls. Conclusions: The spectral differentials depend on the type, population and condition of locally specialized muscular mechanism which can be affected from HPS. The HPS also has a relation to specific cells, such as ICC that generates NO, provoke the spontaneous pacemakers and biological slow waves (Tab. 1, Fig. 1, Ref. 19). Full Text in free PDF www.bmj.sk.
Keywords: pyloric stenosis; L-NAME; Cajall cells; myoelectrical activity